Heterotrimetallic Double Cavity Cages: Syntheses and Selective Guest Binding. Issue 18 (4th March 2022) - Lisboa, Lynn S.; Preston, Dan; McAdam, C. John; Wright, L. James; Hartinger, Christian G.; Crowley, James D.
Abstract: A strategy for the generation of heterotrimetallic double cavity (DC) cages [Pd n Pt m L4 ] 6+ (DC1 : n =1, m =2; and DC2 : n =2, m =1) is reported. The DC cages were generated by combining an inert platinum(II) tetrapyridylaldehyde complex with a suitably substituted pyridylamine and Pd II ions. 1 H and DOSY nuclear magnetic resonance spectroscopy (NMR) and electrospray ionization mass spectrometry (ESIMS) data were consistent with the formation of the DC architectures. DC1 and DC2 were shown to interact with several different guest molecules. The structure of DC1, which features two identical cavities, binding two 2, 6‐diaminoanthraquinone (DAQ ) guest molecules was determined by single‐crystal X‐ray crystallography. In addition, DC1 was shown to bind two molecules of 5‐fluorouracil (5‐FU ) in a statistical (non‐cooperative) manner. In contrast, DC2, which features two different cage cavities, was found to interact with two different guests, 5‐FU and cisplatin, selectively. Abstract : A method for the synthesis of two heterotrimetallic double cavity cages, [Pd n Pt m L4 ] 6+, (where n =1 and m =2 or n =2 and m =1) is described. The cages are shown to interact with several different guest molecules. The cage with two identical cavities can bind two identical guest molecules in a non‐cooperative fashion, whereas the cage with two different cavities can bind two different guests in a segregated manner.